The profile of neurocognitive disorders in patients attending psychiatric outpatient services at a tertiary level academic hospital in Johannesburg - Mngomezulu, Peacemaker Samukelisiwe (My University, 2020)
Mild or major neurocognitive disorders (NCDs) are a group of non-communicable diseases presenting with acquired cognitive decline. They are usually complex, chronic and progressive in nature. NCDs are classified into primary NCDs and secondary NCDs. They are a growing public health concern globally, with the worldwide prevalence of approximately 46.8 million people in 2015. The estimate is expected to increase to 74.7 million by 2030 and 131.5 million in 2050 respectively.The aim of the study was to describe the profile of NCDs in patients attending tertiary level psychiatric outpatient department. The study was a descriptive-retrospective record review of the files of patients who attended the Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) psychiatric outpatient department. Out of 6 879 psychiatric patients that were older than 18 years seen between 01 January 2015 and 31 December 2017, only 145 (2.1%) had a diagnosis of NCD according to DSM IV-TR/DSM-5 criteria. The majority were elderly patients from the 61 - 80 years age group 67 (46.2%), female gender 87 (60%) and of black ethnicity 68 (47%). Most patients presented with major NCDs i.e.129 (89%). Most were secondary in nature 118 (81.1%). Of the primary NCDs frontotemporal NCDs occurred commonly 2 (1.4%). With regards to, secondary NCDs, vascular NCDs 54 (37.2%) and NCDs due to HIV infection 21 (14.5%) were most significantly represented. Cardiovascular diseases 88 (77%), psychotic disorders 54 (39.7%) and major depressive disorders 42 (30.9%) were the most common comorbidities. The study described NCDs in terms of demographic profile, psychiatric and medical comorbidities. The findings support early standardised neurocognitive screening of psychiatric patients for NCDs, to identify those at risk and to prevent rapid progression of those already diagnosed.
A research report submitted in fulfilment of the requirement for the degree of Master of Medicine in the Department of Psychiatry to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020